A study of rice mill innovation for using in household that effects the marketing mix satisfaction of farmers in Thailand - Sawmong, Sudaporn (My University, 2022)
Thailand is a major rice grower and one of the top rice exporters in the world. Thailand's rice is recognized globally for its quality and is in high demand in a large number of countries. Milling is a crucial step in the post-production of rice. The basic objective of a rice milling system is to remove the husk and the bran layers, to produce an edible, rice kernel that is free of impurities. This study focuses on the needs of the farmers to obtain the final product using rice mills as a household item with much-needed innovation. Innovation is defined as a new idea, method, or device. This research aims to develop innovative rice mills for rice farmers, and explores the satisfaction of innovation in rice mill, which is to be used in the households of Thai farmers, and its effect on customer satisfaction as per the 7Ps marketing mix. The instrument used in the survey questionnaire, which was tested by the evaluator, was accurate and had a Cronbach alpha coefficient reliability of 0.958. The statistics used in this study are descriptive statistics, which consist of frequency, percentage, average, and standard deviation. The inferential statistics to test the hypotheses were multiple regression analysis for testing product innovation factors (structure, application, quality, and value) that effect the marketing mix factors (7P's) satisfaction of farmers in Thailand. This research found that the most sought after features in innovative rice mill products for organic farmers are its size, mobility, and cost-effectiveness. It consisted of four innovation factors, which were structure, value, quality, and application. The research found that the farmers focus on the people (staff) most, followed by the product, process, physical evidence, price, place, and promotion, respectively, and that the innovation factor effect on 7P's marketing mixed satisfaction was structure, application, and value of innovation, except quality.